2009
DOI: 10.1080/01411590903372622
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelastic crystals and their nonlinear elastic properties observed in frequency range from gigahertz to milihertz

Abstract: The experiments reported in this article have been performed to unify the results of earlier and recent determinations of parameters describing the elastic properties of Rb 4 LiH 3 (SO 4 ) 4 , LiCsSO 4 (LCS) and KH 2 PO 4 crystals measured by different experimental methods. The above crystals undergo a second-order phase transition, incommensurate phase transition (PT) and a first-order but close to second-order phase transition, respectively. To investigate the elastic properties of the crystals in the freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…The smallness of the softening in the Brillouin experiments compared to those at lower frequency has been noticed also for other FE materials, and explained in terms of dynamic response of the order parameter and domain wall motion [28], but besides relaxation and adiabatic versus isothermal effects, the piezoelectric stiffening from the depolarization field should also be taken into account.…”
Section: Discussionmentioning
confidence: 65%
“…The smallness of the softening in the Brillouin experiments compared to those at lower frequency has been noticed also for other FE materials, and explained in terms of dynamic response of the order parameter and domain wall motion [28], but besides relaxation and adiabatic versus isothermal effects, the piezoelectric stiffening from the depolarization field should also be taken into account.…”
Section: Discussionmentioning
confidence: 65%
“…This indication has been confirmed by Electron Paramagnetic Resonance (EPR) results [16,17]. The study of changes in the elastic properties of the crystal in the range of the phase transition by the method of Dynamic Mechanical Analysis (DMA) [18,19] has revealed an elastic anomaly in the range 190 − 195 K, i.e. at temperatures other than the classical ferroelastic phase transition point.…”
Section: Introductionmentioning
confidence: 66%
“…This phase shows an incommensurate ordering manifested in the Raman scattering spectra by changes in the low-frequency vibrations of the crystal lattice [39]. Moreover, at 196 K a reorganisation of the ferroelastic domain structure was observed [1,16,18], and an additional anomaly in the elastic properties of the crystal was detected by the method of dynamic mechanical analysis [18]. Kurzyński et al, who studied the Ising model in which pseudo-spins corresponded to the rotations of SO 4 tetrahedra, concluded that in the phase below T C the ferroelastic and incommensurate types of ordering co-existed.…”
Section: Phase Coexistence Below T Cmentioning
confidence: 99%
“…The ferroelastic domain structure change was observed in the temperature range 201 K < T < 189 K 19. Below 189 K down to 140 K, the structure remained unchanged.…”
Section: Resultsmentioning
confidence: 90%